2004
DOI: 10.1097/01.ju.0000136430.37245.b9
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF THE DUAL 5α-Reductase INHIBITOR DUTASTERIDE ON MARKERS OF TUMOR REGRESSION IN PROSTATE CANCER

Abstract: In this pilot study dutasteride treatment resulted in almost complete suppression of intraprostatic DHT, increased apoptosis and a trend toward decreased MVD. These findings suggest that short-term treatment with dutasteride can cause regression in some prostate cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 21 publications
4
82
0
1
Order By: Relevance
“…Although the effects of 5␣-reductase inhibitors on known tumors, as opposed to the prevention of new tumors, are unclear, some data suggest that treatment can result in tumor volume reductions. 13 Therefore, the scenario in which an equal reduction in tumor and prostate volume size occurred was also modeled.…”
Section: Modeling the Influence Of Prostate Volume And Tumor Size Redmentioning
confidence: 99%
“…Although the effects of 5␣-reductase inhibitors on known tumors, as opposed to the prevention of new tumors, are unclear, some data suggest that treatment can result in tumor volume reductions. 13 Therefore, the scenario in which an equal reduction in tumor and prostate volume size occurred was also modeled.…”
Section: Modeling the Influence Of Prostate Volume And Tumor Size Redmentioning
confidence: 99%
“…19). Clinical trials also indicated that the combined level of DHT and testosterone was 58% lower in dutasteride than placebo patients (19). Dutasteride similarly causes shrinkage of the prostate gland (20) and atrophy and apoptosis of benign prostatic epithelium and adenocarcinoma in patients with clinically organ-confined prostate cancer (19,20).…”
Section: Reducing the Dihydrotestosterone Environment Associated Withmentioning
confidence: 99%
“…As with finasteride, dutasteride significantly reduces DHT and increases testosterone (versus placebo; ref. 19). Clinical trials also indicated that the combined level of DHT and testosterone was 58% lower in dutasteride than placebo patients (19).…”
Section: Reducing the Dihydrotestosterone Environment Associated Withmentioning
confidence: 99%
See 1 more Smart Citation
“…53 The Reduction by Dutasteride of Prostate Cancer Events (REDUCE) trial showed a decreased volume of HGPIN in a randomized trial of 46 patients who underwent radical prostatectomy that approached statistical significance at P = 0.052. 54 Selective estrogen receptor modulators also show promise in prevent-ing the progression of HGPIN to PCa. In a large phase IIB clinical trial, men with HGPIN who were given 20 mg toremifene had a decreased incidence of PCa at 24.4% versus 31.2% with placebo at 1 year.…”
Section: Impact Of Initial Pathological Findings High Grade Prostaticmentioning
confidence: 99%